2023
DOI: 10.1177/20503121231152324
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and blood pressure control: A preliminary assessment of the role of health insurance in Nigeria and Ghana

Abstract: Objectives: This study sought to assess the current impact of health insurance coverage on medication adherence and blood pressure control of patients being managed for hypertension in Ghana and Nigeria. Methods: The study was a prospective study among 109 patients with hypertension in two health facilities with similar population dynamics in Ghana and Nigeria. Patients were systematically selected, categorized as having health insurance coverage or not, and followed up monthly for 6 months. The outcome variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The findings of the study are also consistent with the study done in eastern Nepal [ 17 ], which identified missed medicines due to high cost as one of the predictors of low level of adherence. It demands the strategies to reduce the high out of pocket expenditure in health such as increasing the coverage of national health insurance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study are also consistent with the study done in eastern Nepal [ 17 ], which identified missed medicines due to high cost as one of the predictors of low level of adherence. It demands the strategies to reduce the high out of pocket expenditure in health such as increasing the coverage of national health insurance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different measures, like a reminder messaging alarm to reduce forgetfulness, counselling to reduce misconceptions about medications, and improving patient education, have been found to be effective improving adherence to antihypertensive medications among patients with hypertension [ 32 , 34 36 ]. However, the effectiveness and feasibility of those interventions in addressing the issue of non-adherence in this context should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%